Answer:
f(x) =
+ 2x³ - 4x² - 6x + 3
Step-by-step explanation:
Note that radical zeros occur in conjugate pairs, thus
- 1 +
is a zero then - 1 -
is also a zero
is a zero then -
is also a zero
Thus the corresponding factors are
(x - (- 1 +
) ), (x - (- 1 -
) ), (x -
), (x - (-
)), that is
(x + 1 -
), (x + 1 +
), (x -
), (x +
)
The polynomial is then the product of the roots
f(x) = (x + 1 -
)(x + 1 +
)(x -
)(x +
)
= ((x + 1)² - (
)²)((x² - (
)²)
= (x² + 2x + 1 - 2)(x² - 3)
= (x² + 2x - 1)(x² - 3) ← distribute
=
- 3x² + 2x³ - 6x - x² + 3
=
+ 2x³ - 4x² - 6x + 3